Determinants of User Satisfaction in The Mypertamina Application With User Engagement as an Intervening Variable - Putra, Gerdathias; Noer, Lissa Rosdiana (Dinasti Publisher, 2025)
The MyPertamina application developed by PT Pertamina aims to enhance the user experience in accessing fuel services in Indonesia. However, despite its widespread use, the application still has some shortcomings. Some users feel that the application does not fully meet their expectations, especially regarding speed, reliability, and the accuracy of the information provided. Additionally, technical issues such as bugs or errors in the application pose barriers that affect user satisfaction, which ultimately impacts the level of user engagement with the application. This study aims to examine how performance expectancy, effort expectancy, social influence, and information quality influence user satisfaction, mediated by user engagement. A survey was conducted among active users of the MyPertamina application who had made transactions using the app. Purposive sampling was used in this study because the researcher wanted to select respondents with specific characteristics, namely active users of the MyPertamina application who had made fuel and non-cash transactions. This study employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with 130 respondents. The results showed that performance expectancy, effort expectancy, social influence, and information quality had a positive and significant impact on user satisfaction, mediated by user engagement. This study provides managerial implications for MyPertamina app developers to continuously improve the app's performance, ease of use, social influence, and the quality of information provided in order to enhance user satisfaction and engagement, thereby supporting sustained app usage. Developers should also pay attention to user feedback regarding technical issues and app quality to enhance the overall user experience.